2020
DOI: 10.1073/pnas.1920036117
|View full text |Cite
|
Sign up to set email alerts
|

Squeezed metallic droplet with tunable Kubo gap and charge injection in transition metal dichalcogenides

Abstract: Shrinking the size of a bulk metal into nanoscale leads to the discreteness of electronic energy levels, the so-called Kubo gap δ. Renormalization of the electronic properties with a tunable and size-dependent δ renders fascinating photon emission and electron tunneling. In contrast with usual three-dimensional (3D) metal clusters, here we demonstrate that Kubo gap δ can be achieved with a two-dimensional (2D) metallic transition metal dichalcogenide (i.e., 1T′-phase MoTe2) nanocluster embedded in a semiconduc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 52 publications
2
29
0
Order By: Relevance
“…As a result, in the heterojunctions of M n H, M ′ n H, and M n N, as n increases, RR increases significantly. This result is in good agreement with previous studies on the heterojunctions based on other 2D materials [ 44 46 ].
Fig.
…”
Section: Resultssupporting
confidence: 93%
“…As a result, in the heterojunctions of M n H, M ′ n H, and M n N, as n increases, RR increases significantly. This result is in good agreement with previous studies on the heterojunctions based on other 2D materials [ 44 46 ].
Fig.
…”
Section: Resultssupporting
confidence: 93%
“…Cai and coworkers calculated the phase diagram of TMDCs as a function of both uniaxial strain and doping and showed that the critical charge doping concentration correlates strongly with the strain exerted to the TMDC. [ 24 ] The interdependent effects of strain and charge doping are directly relevant for intercalation of alkali metals, as we will discuss in the next section.…”
Section: Knowledge Gap In Current Understanding Of Phase Transition and Intercalationmentioning
confidence: 99%
“…[ 36 ] In addition, theoretical calculations predict that in‐plane strain will significantly affect phase transition. [ 24 ] The effects of strain were experimentally observed to delay the lithium staging in several‐layer‐thick graphene flakes. [ 37 ]…”
Section: Knowledge Gap In Current Understanding Of Phase Transition and Intercalationmentioning
confidence: 99%
See 1 more Smart Citation
“…The discovery of graphene and other two-dimensional (2D) layered crystal materials, such as black phosphorus (BP), stanene, transition metal dichalcogenides (TMDS), etc, has triggered great interests in various phenomena in atomically thin space [1][2][3][4][5][6][7][8] . These 2D materials bring about novel electronic and photonic performance different from their counterpart bulk materials due to their electrons, holes and phonons are confined in a small limited space [9][10][11] . As a result of unique physical properties, 2D materials are promising for some innovative applications such as advanced catalyst and nanoelectronic devices 12,13 .…”
Section: Introductionmentioning
confidence: 99%